Light-Powered Self-Adaptive Mesostructured Microrobots for Simultaneous Microplastics Trapping and Fragmentation via in situ Surface Morphing - Ullattil, Sanjay Gopal; Pumera, Martin (Small (Weinheim an der Bergstrasse, Germany), 2023)
Microplastics, which comprise one of the omnipresent threats to human health, are diverse in shape and composition. Their negative impacts on human and ecosystem health provide ample incentive to design and execute strategies to trap and degrade diversely structured microplastics, especially from water. This work demonstrates the fabrication of single-component TiO2 superstructured microrobots to photo-trap and photo-fragment microplastics. In a single reaction, rod-like microrobots diverse in shape and with multiple trapping sites, are fabricated to exploit the asymmetry of the microrobotic system advantageous for propulsion. The microrobots work synergistically to photo-catalytically trap and fragment microplastics in water in a coordinated fashion. Hence, a microrobotic model of "unity in diversity" is demonstrated here for the phototrapping and photofragmentation of microplastics. During light irradiation and subsequent photocatalysis, the surface morphology of microrobots transformed into porous flower-like networks that trap microplastics for subsequent degradation. This reconfigurable microrobotic technology represents a significant step forward in the efforts to degrade microplastics.
Keywords: microrobots; microplastics; TiO2; micromotors; surface morphology